Social Cognition in Neurodevelopmental Disorders and Epilepsy - Pastorino, Grazia Maria Giovanna; Operto, Francesca Felicia; Padovano, Chiara; Vivenzio, Valentina; Scuoppo, Chiara; Pastorino, Nazareno; Roccella, Michele; Vetri, Luigi; Carotenuto, Marco; Coppola, Giangennaro (Frontiers in neurology, 2021)
Introduction: The purpose of our study was to perform a comparative analysis of social cognition in children and adolescents with epilepsy, autism spectrum disorder (ASD), specific learning disorder (SLD) and in typical development (TD) controls. The secondary aim was to relate social cognition to some clinical and demographic characteristics. Methods: Our work is a transversal observational study. The recruits were 179 children and adolescents aged between 6 and 18 years diagnosed with epilepsy, ASD, or SLD and 32 subjects with TD. All the participants underwent neuropsychological assessment of Emotion Recognition (ER) and Theory of Mind (ToM) skills. Results: All three clinical groups performed significantly worse than controls in ER and ToM. The ASD group achieved significantly lower performance than the other groups; however, the scores of SLD and epilepsy groups were comparable. The ER performances are related to non-verbal intelligence only in the group with epilepsy. Conclusion: Children and adolescents with focal epilepsy, SLD, or ASD may present a deficit of varying extent in emotion recognition and ToM, compared with TD peers. These difficulties are more pronounced in individuals with ASD, but impairment worthy of clinical attention also emerges in individuals with SLD and epilepsy.